The effect of ploidy and temporal changes in the biochemical profile of gibel carp (Carassius gibelio): a cyprinid fish species with dual reproductive strategies - Vetešník, Lukáš; Halačka, Karel; Simková, Andrea (Fish physiology and biochemistry, 2013)
The basic biochemical profile of gibel carp (Carassius gibelio), diploid-triploid cyprinid species complex with dual reproduction modes, was investigated. The aim of the study was to test for the effect of fish group (which combines the effects of ploidy and sex) and temporal changes on indicators of the biochemical profile of blood in gibel carp. We showed that the basic biochemical profile of blood is significantly influenced by season and fish group. Triploid gynogenetic females had a better condition measured by total protein concentration than sexual diploids. The higher concentrations of triacylglycerols and cholesterol in triploid females when compared to diploids indicate a higher metabolic rate and higher energy intake during the whole year, which may represent a disadvantage for triploids. Differences in the concentrations of blood biochemical analytes between triploid females and diploids suggest a potential difference in the regulation of a wide range of physiological and biochemical processes in which these analytes participate. The biochemical profiles of two forms of C. gibelio could at least partially explain the changes of character of its naturally occurring populations.
Keywords: Seasons; Reproduction; Triglycerides; krevní proteiny; Česká republika; sexuální faktory; Blood Proteins; mužské pohlaví; kapři; Cholesterol; Czech Republic; Blood Chemical Analysis; ploidie; Carps; biochemická analýza krve; ženské pohlaví; zvířata; Ploidies; Sex Factors; triglyceridy; rozmnožování; Female; roční období; Male; cholesterol; Animals